Surdez, redes sociais e aplicativo de interação - Sehnem, Rodrigo (2012)
The computer as an auxiliary tool in the teaching and learning, allows students to experience situations that facilitate the development of their capabilities in the new information society and new forms of interaction in educational contexts. When it comes to people with special educational needs, digital technologies can enhance the ability of communication and learning. In this paper, we show that it is possible to interact via software even with a hearing impairment. For this, we present a tool that enables this interaction with the computer through the transformation of spoken words to pounds.